1999
DOI: 10.4269/ajtmh.1999.60.752
|View full text |Cite
|
Sign up to set email alerts
|

No serologic evidence of an association found between Gulf War service and Mycoplasma fermentans infection.

Abstract: Abstract. Occult occupational infection with Mycoplasma fermentans has been proposed as a cause for illness among Persian Gulf War veterans. Symptom data and sera from a 1994-1995 cross-sectional survey of Navy Seabees were used to select symptomatic and asymptomatic Gulf War veterans and nondeployed veterans to evaluate this hypothesis. Survey sera from 96 Seabees were matched to prewar (before September 1990) archived sera. Immunoblot serologic analyses were performed for M. fermentans in a controlled, blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…There are few other groups of organisms that have been as controversial as mycoplasmas in having their pathogenic niche defined (Baseman and Tully, 1997), particularly in man, where they have been linked over recent years to conditions such as Crohn's disease, chronic fatigue syndrome, a variety of arthritides and even Gulf War Syndrome, although the last possibility is now disproved (Nicolson and Nicolson, 1996;TaylorRobinson, 1996;Gray et al, 1999;Hart et al, 2002;Nijs et al, 2002;Roediger and Macfarlane, 2002;Endresen, 2003). However, the disease potential of many of the mycoplasmas of veterinary importance has been well established and more clearly defined (Taylor-Robinson and Bradbury, 1998).…”
Section: The Role Of Mycoplasmas In Diseasementioning
confidence: 99%
“…There are few other groups of organisms that have been as controversial as mycoplasmas in having their pathogenic niche defined (Baseman and Tully, 1997), particularly in man, where they have been linked over recent years to conditions such as Crohn's disease, chronic fatigue syndrome, a variety of arthritides and even Gulf War Syndrome, although the last possibility is now disproved (Nicolson and Nicolson, 1996;TaylorRobinson, 1996;Gray et al, 1999;Hart et al, 2002;Nijs et al, 2002;Roediger and Macfarlane, 2002;Endresen, 2003). However, the disease potential of many of the mycoplasmas of veterinary importance has been well established and more clearly defined (Taylor-Robinson and Bradbury, 1998).…”
Section: The Role Of Mycoplasmas In Diseasementioning
confidence: 99%
“…But in one published study of this hypothesis, no association was found between Mycoplasma fermentans infection and either deployment to the Arabian Gulf or postwar symptoms. 49 Another study is in progress to determine if proposed diagnostic tests for Mycoplasma infection, which utilize polymerase chain reaction (PCR), can identify Gulf War veterans with chronic unexplained illness. 50 The other hypothesis being studied involves the possibility of a chronic, systemic gram-positive coccal infection among Gulf War veterans.…”
Section: Endemic Infectious Diseasesmentioning
confidence: 99%
“…5,6 Along the way, a number of hypotheses fell by the wayside or remained ensnared in a web of ambiguity. The Mycoplasma theory promoted primarily by Nicolson 7 has not been confirmed 8 ; in fact, a multicenter study found no evidence of mycoplasmas as the etiology of veterans' complaints and found doxycycline to be no better than placebo at improving symptoms and functional measures. 9 Reports from Haley's group of well-defined illness clusters related to exposure to chemical weapons, insect repellents, and pyridostigmine bromide 10 (used prophylactically to neutralize the toxicity of chemical agents) have not been replicated by other researchers, [11][12][13] and the Seabee cohorts that were studied look increasingly like outliers not representative of Gulf War veterans as a whole.…”
mentioning
confidence: 98%